The use of the term "heresy" in an ecumenical perspective - Godlewski, Karol (Studia Teologiczne Białystok Drohiczyn Łomża, 2022)
The term "heresy" has been used quite commonly in the language of religious studies and theology practically since the beginning of the history of these sciences. It carries a stigmatizing judgment that places a given person, view, or group of people outside of orthodoxy. The use of this concept must therefore be carefully balanced and justified. The contemporary ecumenical perspective shows that this balance and justification are often lacking. Based on the history of Christianity, canon law and dogmatic theology, this article aims to show the proper semantic scope of the term "heresy" and to prove that the application of this term by Catholics to non-Catholic Christian denominations is unauthorized. The ecumenical perspective constituting the background of the article also demands that the presented work emphasizes that the features of heresy are exhausted by the negation of the ecumenical aspirations of the Church.